2017
DOI: 10.1038/bmt.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial bloodstream infections in the allogeneic hematopoietic cell transplant patient: new considerations for a persistent nemesis

Abstract: Bacterial bloodstream infections (BSI) cause significant transplant-related morbidity and mortality following allogeneic hematopoietic cell transplantation (allo-HCT). This manuscript reviews the risk factors for and the bacterial pathogens causing BSIs in allo-HCT recipients in the contemporary transplant period. In addition, it offers insight into emerging resistant pathogens and reviews clinical management considerations to treat and strategies to prevent BSIs in allo-HCT patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
51
4
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 164 publications
(194 reference statements)
6
51
4
3
Order By: Relevance
“…This includes tracking not only CLABSI (stratified by MBI‐LCBI vs non–MBI‐LCBI) and secondary BSI, but also SPBC with NHSN‐defined common commensals. The inclusion of SPBC is relevant since these can be real BSI in immunocompromised patients . Although there has been progress in the reduction of CLABSI rates using quality improvement methodologies across pediatric centers, the majority of data describing outcomes after BSI in these high‐risk populations is limited to single‐center reviews.…”
Section: Introductionmentioning
confidence: 99%
“…This includes tracking not only CLABSI (stratified by MBI‐LCBI vs non–MBI‐LCBI) and secondary BSI, but also SPBC with NHSN‐defined common commensals. The inclusion of SPBC is relevant since these can be real BSI in immunocompromised patients . Although there has been progress in the reduction of CLABSI rates using quality improvement methodologies across pediatric centers, the majority of data describing outcomes after BSI in these high‐risk populations is limited to single‐center reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial bloodstream infections (BSIs) are a common infectious complication following stem cell transplantation (SCT) in both pediatric and adult populations . The majority of BSI occurs during the preengraftment period and is associated with prolonged hospitalization, intensive care unit admission, and protracted antibiotic exposure, leading to increased morbidity and mortality .…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial bloodstream infections (BSIs) are a common infectious complication following stem cell transplantation (SCT) in both pediatric and adult populations . The majority of BSI occurs during the preengraftment period and is associated with prolonged hospitalization, intensive care unit admission, and protracted antibiotic exposure, leading to increased morbidity and mortality . In particular, it has recently been shown that patients who have more than one BSI within the first year following SCT have a higher rate of nonrelapsed mortality (NRM) than patients experiencing a single BSI …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis and septic shock from bloodstream infections (BSI) are a growing health care burden in hospitalized pediatric oncology and hematopoietic stem cell transplant (HSCT) patients . BSI occur in nearly 30% of patients undergoing HSCT and are associated with prolonged hospitalization, septic shock, increased rates of intensive care admission, prolonged antibiotic treatment, and increased mortality . Fever is often the first symptom of sepsis, and initiation of broad‐spectrum antibiotics within 60 min of recognition of sepsis or septic shock has been shown to improve morbidity and mortality .…”
Section: Introductionmentioning
confidence: 99%